Shared and Unique Patterns of DNA Methylation in Systemic Lupus Erythematosus and Primary Sjögren's Syndrome - Imgenberg-Kreuz, Juliana; Almlöf, Jonas Carlsson; Leonard, Dag; Sjöwall, Christopher; Syvänen, Ann-Christine; Rönnblom, Lars; Sandling, Johanna K.; Nordmark, Gunnel (Frontiers in Immunology, 2019)
OBJECTIVES To perform a cross-comparative analysis of DNA methylation in patients with systemic lupus erythematosus (SLE), patients with primary Sjögren’s syndrome (pSS) and healthy controls addressing the question of epigenetic sharing and aiming to detect disease-specific alterations. METHODS DNA extracted from peripheral blood from 347 cases with SLE, 100 cases with pSS and 400 healthy controls were analysed on the HumanMethylation 450k array, targeting 485,000 CpG sites across the genome. A linear regression model including age, sex and blood cell type distribution as covariates was fitted, and association p-values were Bonferroni corrected. A random forest machine learning classifier was designed for prediction of disease status based on DNA methylation data. RESULTS We established a combined set of 4,945 shared differentially methylated CpG sites (DMCs) in SLE and pSS compared to controls. In pSS, hypomethylation at type I interferon induced genes was mainly driven by patients who were positive for Ro/SSA and/or La/SSB autoantibodies. Analysis of differential methylation between SLE and pSS identified 2,244 DMCs with a majority of sites showing decreased methylation in SLE compared to pSS. The random forest classifier demonstrated good performance in discerning between disease status with an area under the curve (AUC) between 0.83 and 0.96. CONCLUSIONS The majority of differential DNA methylation is shared between SLE and pSS, however, important quantitative differences exist. Our data highlights neutrophil dysregulation as a shared mechanism, emphasizing the role of neutrophils in the pathogenesis of systemic autoimmune diseases. The current study provides evidence for genes and molecular pathways driving common and disease-specific pathogenic mechanisms.